The Influence of Digital Banking, Company Characteristics and Capital Structure on Banking Financial Resilience with Good Corporate Governance as an Intervening Variable in Conventional Commercial Banks Listed in the LQ45 Index on the Indonesia Stock Exchange - Alfons, Susana K.; Hwihanus; R. Pandin, Maria Yovita (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The banking sector is facing complex transformations due to the digital technology revolution, the evolution of consumer preferences, and intense competition from fintech entities that create an increasingly challenging business landscape. The acceleration of banking digitalization presents new challenges in the form of cyber risk exposure, financial market volatility, and the imperative to strengthen corporate governance to ensure operational continuity and long-term sustainability. This study aims to analyze the influence of digital banking, company characteristics, and capital structure on banking financial resilience with Good Corporate Governance (GCG) as an intervening variable in conventional commercial banks listed in the LQ45 Index on the Indonesia Stock Exchange. The research method uses a quantitative approach with an explanatory research design that adopts purposive sampling techniques for five conventional banks (Bank Central Asia, Bank Negara Indonesia, Bank Rakyat Indonesia, Bank Mandiri, and Bank Tabungan Negara) for the 2019- 2023 period. Data analysis used Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS software version 4.1.1.2 to evaluate measurement models and structural models. The results of the study show that digital banking does not have a significant effect on GCG or banking financial resilience, while company characteristics have a significant positive effect on financial resilience and negative on GCG. Capital structure has a significant negative effect on GCG but not significantly on financial resilience. GCG has not been proven to be an effective intervening variable in strengthening the relationship between independent variables and financial resilience. The research concludes that internal factors of the company have a dominant role in determining the financial resilience of banks compared to digital technology innovations, so banking institutions need to integrate digitalization strategies with strengthening internal fundamentals and comprehensive GCG implementation.